ABREVIASI DALAM PERCAKAPAN SEHARI-HARI DI MEDIA SOSIAL: SUATU KAJIAN MORFOLOGI - Rengganis Citra Cenderamata; Agus Nero Sofyan (Kajian Linguistik dan Sastra, 2019)
This article aims to describe a process of abbreviation occurred in the daily conversation through social media. The method used in this research is qualitative method. The data was taken from daily conversation through social media, such as line, whats app, facebook, twitter, and Instagram. The theory is that there is an abbreviation process and slang language in the conversation. The main main of this research is to describe the general features and the abbreviation processes used by the younger generation and the older generation from the Indonesian social media community. The result shows that there are three abbreviation processes, namely acronym, shortening, and word fragmentation. Among the three, acronym is the most common. The reason for this is that the speakers are intended to safe time, fill in the gap f communication, and to show social strata.Keywords: abbreviation, morphology, social media